Art of death and life - Irarrázaval, Diego (1994)
The artistic sensibility of the Andean population points to its future and that of humanity. Faced with the globalization of some human behaviors (and the exclusion of others), a people exercises its freedom by being as it is and, therefore, by being different. This freedom has characterized Andean communities. I am going to dwell on two dimensions: everyday art around death-life and some elaborations around violence-peace. When examining these languages, we ask ourselves what they say about the future not only of these peoples but of all human beings.